2017
DOI: 10.1021/acs.iecr.7b02004
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxygen Removal from Seawater in Industrial Scale Using Silver Cathode

Abstract: In this study, electrochemical removal of oxygen from seawater in industrial scale is demonstrated. A test rig with an industrial scale electrochemical cell has been constructed and tested with filtrated oxygen rich seawater. The electrochemical cell was comprised of a silver mesh cathode and an iridium oxide anode with a cation exchange membrane. The effects of flow rate, pressure, and applied voltage on oxygen removal efficiency and resulting current were studied. Also, the differential pressure between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This method avoids the use of additional chemicals and utilizes only seawater as an electrolyte. The electrochemical system with a silver cathode for oxygen removal works efficiently on both the laboratory scale and the industrial scale, as previously reported by Dotel et al [1,2].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…This method avoids the use of additional chemicals and utilizes only seawater as an electrolyte. The electrochemical system with a silver cathode for oxygen removal works efficiently on both the laboratory scale and the industrial scale, as previously reported by Dotel et al [1,2].…”
Section: Introductionsupporting
confidence: 76%
“…In our previous work, seawater was used both as an anolyte and catholyte [2]. The pH of the anolyte and catholyte were the same and, during operations, the anolyte became acidic and the catholyte became alkaline.…”
Section: Assessment Of Anolytes For Industrial Deoxygenation Cellmentioning
confidence: 99%